What we can learn from invertebrate learning. - Krasne, Franklin B.; Glanzman, David L. (Annual Review of Psychology, 1995)
An analysis of what can be learned from invertebrate learning. Research on what invertebrates learn is discussed in terms of physiologically analyzed learning paradigms and the choice of paradigms studied. In addition, studies on the loci of functional changes responsible for learning in such invertebrates as Aplysia, crayfish, Hermissenda, and insects are outlined, and the role of intrinsic change, extrinsic modulation, and parallel distributed processing in invertebrate learning is considered. A discussion is provided on the induction of neuronal changes responsible for learning in invertebrates, the development of memory in invertebrates, and factors related to the functional expression of engrams in invertebrates, such as altered ion channels, undefined physiological changes, and anatomical change.